Differentiation and subpopulation composition of VEGFR2+ cells in the blood and bone marrow in ischemic cardiomyopathy - S. P. Chumakova; O. I. Urazova; V. M. Shipulin; O. A. Denisenko; T. E. Kononova; K. V. Nevskaya; S. L. Andreev (Бюллетень сибирской медицины)
Aim. To identify disturbances of differentiation and subpopulation composition of VEGFR2+ cells in the blood and bone marrow associated with the features of the cytokine profile in the blood and bone marrow in patients with coronary artery disease (CAD) with and without ischemic cardiomyopathy (ICM).Materials and methods. The study included 74 patients with СAD with and without ICM (30 and 44 people, respectively) and 18 healthy donors. In all patients with СAD, peripheral blood sampling was performed immediately before coronary artery bypass grafting, and bone marrow samples were taken during the surgery via a sternal incision. In the healthy donors, only peripheral blood sampling was performed. In the bone marrow and blood samples, the number of VEGFR2+ cells (CD14+VEGFR2+ cells) and their immunophenotypes CD14++CD16-VEGFR2+, CD14++CD16+VEGFR2+, CD14+CD16++VEGFR2+, and CD14+CD16-VEGFR2+ was determined by flow cytometry. Using enzyme-linked immunosorbent assay, the levels of VЕGF-А, TNFα, M-CSF, and IL-13, as well as the content of MCP-1 (only in the blood) and the M-CSF / IL-13 ratio (only in the bone marrow) were determined.Results. The content of CD14+VEGFR2+ cells in the blood of CAD patients with and without ICM was higher than normal values due to the greater number of CD14++CD16-VEGFR2+, CD14++CD16+VEGFR2+, and CD14+CD16++VEGFR2+. In the bone marrow of the patients with ICM, the content of CD14++CD16-VEGFR2+, CD14+CD16++VEGFR2+, and CD14+CD16-VEGFR2+ was lower than in patients with CAD without ICM, and the number of CD14++CD16+VEGFR2+ cells corresponded to that in the controls. Regardless of the presence of ICM in CAD, a high concentration of TNFα and normal levels of VEGF-A and IL-13 were observed in the blood. In CAD without ICM, an excess of MCP-1 and deficiency of M-CSF were revealed in the blood. In the bone marrow, the levels of VEGF-A, TNFα, M-CSF, and IL-13 were comparable between the groups of patients against the background of a decrease in the M-CSF / IL-13 ratio in the patients with ICM.Conclusion. Unlike CAD without cardiomyopathy, in ICM, no excess of VEGFR2+ cells and MCP-1 in the blood is observed, which hinders active migration of CD14+CD16++VEGFR2+ cells from the myeloid tissue, and a decrease in the M-CSF / IL-13 ratio in the bone marrow disrupts differentiation of other forms of VEGFR2+ cells, preventing vascular repair.